Isolation and characterization of outer membrane permeability mutants in Escherichia coli K-12. - Benson, S A (1985)
Escherichia coli normally requires the lamB gene for the uptake of maltodextrins. We have identified and characterized three independent mutations that allow E. coli to grow on maltodextrin in the absence of a functional lamB gene by allowing maltodextrins with a molecular weight greater than 1,000 to cross the outer membrane barrier. Two of the mutations map to the structural gene for the outer membrane porin OmpF, and the remaining mutation maps to the structural gene for the second major outer membrane porin, OmpC. These mutations increase the permeability of the outer membrane to small hydrophilic substances, antibiotics, and detergents. These mutations alter the electrophoretic mobility of the respective porin proteins.